Critique et discipline - Renaud Debailly (Revue d’Histoire des Sciences Humaines)
We propose to study here the connections between science studies and the radical critique of science which emerges in different scientific communities from May 68. By tracing the evolution of these critical movements, the trajectories of certain actors and changes in the sociology of science in France, our aim is to identify areas of convergence and to understand the consequences of this convergence for the sociology of science.